The first 24-hour bilirubin level as a predictor of hyperbilirubinemia in healthy term newborns - Rina Triasih; Ekawaty L Haksari; Achmad Surjono (Indonesian Pediatric Society, 2003)
Background Early discharging healthy term newborns results ina difficulty to recognize hyperbilirubinemia.Objective The aim of this study was to determine the value of thefirst 24-hour total and unbound bilirubin levels in predicting hyper-bilirubinemia in healthy term newborns.Methods The first 24-hour and the 5 th day total and unboundbilirubin levels were measured in 84 healthy term newborns. Thetotal bilirubin level was measured spectrophotometrically, whereasunbound bilirubin level was determined by peroxidase-oxidationmethod. Hyperbilirubinemia was defined as serum total bilirubin of>12.9 mg/dL or serum unbound bilirubin of >0.5 mg/dL after 24hours of life.Results A correlation between the first 24-hour and the 5 th daytotal bilirubin levels was found (r= 0.53) with a regression equa-tion: Y (total bilirubin on day 5) = 4.69 + 1.15X (total bilirubin in thefirst 24 hours). In unbound bilirubin (r=0.31), the regression equa-tion was Y (unbound bilirubin on day 5) = 0.13 + 0.95X (unboundbilirubin in the first 24-hours). The relative risk for developing hy-perbilirubinemia in newborns whose TB 1 was >4.5 mg/dL was 12(95% CI 2.9;48.4), whereas newborns whose UB 1 was >0.09 mg/dL was 9.5 (95% CI 1.2;77.4).Conclusion Total bilirubin level of >4.5 mg/dL in the first 24 hourscan predict the development of hyperbilirubinemia in term new-borns in the first week of life. Newborns with such level of totalbilirubin need a longer stay or should visit the hospital on day 5-7